Operation power consumption and verification tests of a trenching device for orchards in Xinjiang based on discrete element - Ma, Chen; Qi, Jiangtao; Kan, Za; Chen, Shaojie; Meng, Hewei (International Journal of Agricultural and Biological Engineering, 2021)
According to the agronomic requirements of orchard planting pattern and fertilization in Xinjiang, the soil particle models and a soil-trenching device interaction model were established by using discrete element simulation software in order to find out the law of influence of structure parameters and working parameters on the operation power consumption of a segmented cutting trenching device; moreover, its cutting process was simulated according to the response surface test design. According to the results of research on the influence of forward speed, cutter disk speed and cutter disk combination on the operation power consumption of the segmented cutting trenching device, the law of their influence on the operation power consumption in descending order is forward speed, cutter disk combination, cutter disk speed. According to the response surface test result, the following influential factor parameter combination has been obtained: forward speed 815 m/h, cutter disk speed 112 r/min, cutter disk combination A (cut angle 150°, bent angle 60° and working width 133 mm), cutter disk combination B (cut angle 180°, bent angle 90° and working width 166 mm), and trenching operation power consumption-optimization results were verified through field tests. According to the verification, the results showed a high accuracy of the simulation, with a relative error mean of 3.18% between the theoretical value and the field test value. This study can provide a reference for the energy-saving design of orchard trenching devices. Keywords: trenching device, discrete element, orchard, power consumption, simulation analysis, parameter optimization DOI: 10.25165/j.ijabe.20211401.5477 Citation: Ma C, Qi J T, Kan Z, Chen S J, Meng H W. Operation power consumption and verification tests of a trenching device for orchards in Xinjiang based on discrete element. Int J Agric & Biol Eng, 2021; 14(1): 133–141.